Validation of SPARCC MRI-RETIC e-tools for increasing scoring proficiency of MRI sacroiliac joint lesions in axial spondyloarth - Maksymowych, Walter; Hadsbjerg, Anna Enevold Fløistrup E F; Østergaard, Mikkel; Micheroli, Raphael; Pedersen, Susanne Juhl; Ciurea, Adrian; Vladimirova, Nora; Nissen, Michael S; Bubova, Kristyna; Wichuk, Stephanie; de Hooge, Manouk; Mathew, Ashish J; et al. (RMD open, 2024)
BACKGROUND: The Spondyloarthritis Research Consortium of Canada (SPARCC) developers have created web-based calibration modules for the SPARCC MRI sacroiliac joint (SIJ) scoring methods. We aimed to test the impact of applying these e-modules on the feasibility and reliability of these methods. METHODS: The SPARCC-SIJ RETIC e-modules contain cases with baseline and follow-up scans and an online scoring interface. Visual real-time feedback regarding concordance/discordance of scoring with expert readers is provided by a colour-coding scheme. Reliability is assessed in real time by intraclass correlation coefficient (ICC), cases being scored until ICC targets are attained. Participating readers (n=17) from the EuroSpA Imaging project were randomised to one of two reader calibration strategies that each comprised three stages. Baseline and follow-up scans from 25 cases were scored after each stage was completed. Reliability was compared with a SPARCC developer, and the System Usability Scale (SUS) assessed feasibility. RESULTS: The reliability of readers for scoring bone marrow oedema was high after the first stage of calibration, and only minor improvement was noted following the use of the inflammation module. Greater enhancement of reader reliability was evident after the use of the structural module and was most consistently evident for the scoring of erosion (ICC status/change: stage 1 (0.42/0.20) to stage 3 (0.50/0.38)) and backfill (ICC status/change: stage 1 (0.51/0.19) to stage 3 (0.69/0.41)). The feasibility of both e-modules was evident by high SUS scores. CONCLUSION: The SPARCC-SIJ RETIC e-modules are feasible, effective knowledge transfer tools, and their use is recommended before using the SPARCC methods for clinical research and tria.
Keywords: magnetická rezonanční tomografie; Spondylarthritis; Kanada; Magnetic Resonance Imaging; Reproducibility of Results; Humans; Sacroiliac Joint; Canada; reprodukovatelnost výsledků; sakroiliakální kloub; spondylartritida; lidé